Reading real person fiction as digital fiction: An argument for new perspectives. (December 2018) - Fathallah, Judith
'Real person fiction' (RPF) is a subset of fanfiction that has gone largely unnoticed by academics. A handful of articles have argued for the justification of stories about real (living) people as a legitimate and morally sound art form, but only a very few studies have begun to consider RPF as a genre with its own aesthetics and conventions. This article argues that, to understand fannish RPF, we need to incorporate tools developed by scholars of digital fiction. Almost all fanfic is now produced for and on digital platforms, and moreover, the natural fit between RPF specifically and the study of metalepsis, or self-conscious movement between 'levels' of reality and fiction, makes this tool and others imported from the study of digital fiction an illuminating set of lenses through which read it. Along the way, I will incorporate further narrative theory to suggest that we understand appeals to the putative subject of RPF as directed to a 'fictiona lized addressee', that is, an addressee who is neither purely fictional nor purely nonfictional, but a construct of mediated activity that demonstrates fandom's participation in the construction of the subcultural celebrity.